Editorial - Abdul Rahim, Ezamin (The Interventionalist Journal, 2021)
On behalf of the editorial board of The Interventionalist Journal (TIJ), I would like to extend my deepest appreciation to the founder team, who had built the foundation of this journal. The aim of The Interventionalist Journal is to provide and served as a platform for all clinicians who are doing minimally invasive procedures to share their findings, expertise, innovations and experiences at the regional and international significance. We envisaged being providing a high‑standard and evidence‑based platform for publishing high impact publications. I am humbly inviting each of you to actively participate and contribute to The Interventionalist Journal as an author, reviewer, and reader. The Interventionalist Journal has a strong starting point and I am confident that, we can eventually venture into new heights. Sincerely, Ezamin Abdul Rahim, MD, MMed Rad Editor-in-Chief The Interventionalist Journal